1964
DOI: 10.1128/jb.88.1.261-262.1964
|View full text |Cite
|
Sign up to set email alerts
|

ELIMINATION OF PENICILLIN RESISTANCE OF STAPHYLOCOCCUS AUREUS BY TREATMENT WITH ACRIFLAVINE

Abstract: FIG. 1. Fluorescent-antibody stainingi of Bacillus anthracis in a tissue imprint of dried meat. Due to the intense staining of the large quantity of capsular material, the organisms have a hazy appearance. 1,250 X. diagnosis of anthrax, since the organisms can test. Attention should be given to the epidemibe detected with rapidity in the tissues and ological and clinical features of the disease, since lesions. Therapeutic and control measures then the fluorescence of some nonpathogenic, gramcan be instituted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
1

Year Published

1965
1965
1972
1972

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 0 publications
3
34
0
1
Order By: Relevance
“…Many papers have described the unstable resistance in staphylococci including the resistance to macrolide antibiotics [11,13,16], TC [1,8,10], PC [2,3,7,9,13,15], kanamycin [4] and chloramphenicol [4,9]. The first results of irreversible elimination of resistance to macrolide (Mac) antibiotics led us to the conclusion that the determinant responsible for Mac-resistance in staphylococci is located extrachromosomaly, probably being on a plasmid [11,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many papers have described the unstable resistance in staphylococci including the resistance to macrolide antibiotics [11,13,16], TC [1,8,10], PC [2,3,7,9,13,15], kanamycin [4] and chloramphenicol [4,9]. The first results of irreversible elimination of resistance to macrolide (Mac) antibiotics led us to the conclusion that the determinant responsible for Mac-resistance in staphylococci is located extrachromosomaly, probably being on a plasmid [11,16].…”
Section: Discussionmentioning
confidence: 99%
“…The first results of irreversible elimination of resistance to macrolide (Mac) antibiotics led us to the conclusion that the determinant responsible for Mac-resistance in staphylococci is located extrachromosomaly, probably being on a plasmid [11,16]. According to transduction analysis and genetic investigation, it was concluded that there were probably two plasmids; one carrying a PC-resistance determinant and another harboring both PC-and Mac-re-sistance determinants [7,[13][14][15][16]. Thereafter, many papers presented further proof that the genetic determinants for drugresistance in staphylococci are located on plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, a variety of ordinarily nonmutagenic agents have been found to promote the appearance of penicillinase-negative variants in cultures of penicillinase-positive staphylococci. Among these agents are heat (Bondi et aE., 1953) ; novobiocin (Novick, 19636) ; quinine, tetracycline, glucose, and certain detergents (Borowski, 1964) ; and acridine dyes (Harmon & Baldwin, 1964;Hashimoto et al, 1964). In none of these cases can the distinction be made on the basis of available evidence between "curing" and the selection of spontaneous negatives.…”
Section: Similar Types Of Experiments Have Indicated That the Inducibmentioning
confidence: 99%
“…It has been demonstrated that the genetic determinant of penicillinase (PC-ase) formation in Staphylococcus aureus is incorporated in an extrachromosomal element (plasmid) [3,5]. On the other hand, Asheshov [1] has presented evidence suggesting that the genetic determinant for PC-ase formation in a strain of S. aureus is chromosomally located.…”
mentioning
confidence: 99%